Kajian Sistem Permintaan Pangan Di Indonesia - Handewi P.S. Rachman; nFN Erwidodo (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1994)
This paper is aimed at analyzing food demand system in Indonesia using the 1990's National Socio-Economic Survey (SUSENAS) data. Using an Almost Ideal Demand System (AIDS), the food demand parameters and elasticities were estimated both in aggregated and disaggregated levels, that is an urban-rural and household's income disaggregation, respectively. The results show that during 1987-1990 period, the share of food expenditure in general has been declining relative to non-food, indicating an increasing welfare of the society. Nevertheless, the increase in welfare appears to be enjoyed by urban citizen than those living in the rural areas. This conclusion is also supported by the fact that the expenditure shares on protein-food (fish, meat, eggs, milk, and legumes) in urban area are higher than those in the rural area. The analysis found that: (1) the price demand elasticity for a number of food groups, including cereals and tuber, tend to decline as income increasing, (2) the income elasticity of demand for cereals is lower as income levels get higher, and the opposite is true for the protein-sources of food. The results of this analysis is therefore confirm that increasing income of the society will go along with the promotion of food diversification in consumption.